Comparing the Effectivities of Chitosan Citrate and Chitosan Acetate in Eradicating Enterococcus faecalis Biofilm - Uppalavanna Witedja; Tien Suwartini; Anastasia E Prahasti; Armelia Sari Widyarman (Faculty of Dentistry, Universitas Trisakti, 2018)
Background: Adequate biomechanical preparations, antibacterial irrigants, and intracanal medications to promote the elimination of bacteria and their products are required to succeed root canal treatment. Enterococcus faecalis with its biofilm is known as an important etiological agent in endodontic treatment failures. Chitosan, as a natural product, has an antibacterial activity and is considered less toxic to the periapical tissue than other irrigants. However, the use of this natural product needs to be examined to determine its effectiveness as a root canal irrigant in endodontic treatment; this can be done by comparing it with the most common endodontic irrigant (NaOCl 5.25%) as a positive control. Objective: The objective of the study was to compare the effectiveness between 1–3% chitosan acetate (CA) and 1–3% chitosan citrate (CC) against E. faecalis biofilm formation after treatment for 15, 30, and 60 minutes. Methods: The study was conducted using 12 groups, including 1–3% CA, 1–3% CC, and control groups. E. faecalis biofilms in 96-well plates were exposed to each sample for 15, 30, or 60 minutes. Subsequently, the biofilms were stained with crystal violet solution, and the optical density value was measured using a microtiter plate reader at a wavelength of 600 nm. Results: CA and CC were effective in eradicating E. faecalis biofilm. However, the levels of effectiveness of CC and CA depended on the concentration and application time. Three-way analysis of variance (ANOVA) showed a significant difference between the irrigants (p <0.05) and three application times (p <0.05). The CA was effective in eradicating biofilm after 15 minutes of application, whereas the CC was more effective after 30 and 60 minutes of application. Conclusion: CC and CA are both effective in eradicating E. faecalis biofilm.